Harmonizing Philippine census data across decades (1970-2020) - Kris Ann M. Melad (Philippine Institute for Development Studies (PIDS), 2024)
This research harmonizes Philippine Census of Population and Housing (CPH) data from 1970 to 2020 to address data consistency challenges across five decades. The study systematically reconciles evolving variable definitions, classification systems, and measurement scales to create a unified longitudinal dataset. Key harmonization challenges include accommodating education system changes such as the K-12 reforms, tracking administrative boundary modifications through the years, managing expanding data scope across census years, and handling historical data preservation issues, particularly for the 1970 and 1980 censuses. The research involved creation of translation tables and crosswalks for major classification systems including the Philippine Standard Geographic Classification (PSGC), Philippine Standard Occupational Classification (PSOC), and Philippine Standard Industrial Classification (PSIC). Variable-specific harmonization protocols and guidelines for researchers using the harmonized data are also documented. The harmonization process standardized core demographic variables across all periods while preserving more detailed classifications where possible, though some variables necessarily lost granularity when harmonized to their lowest common denominator. Beyond producing a consistent dataset for longitudinal analysis, this study contributes to PIDS's agenda of strengthening statistical systems for evidence-based policymaking. The paper concludes with recommendations for improving future census data collection and harmonization practices to support effective policy development in the Philippines.
Keywords: 330; census; data harmonization; variable standardization; data translation; Philippine Statistical System